Layout Design Plan for PT. Golden Sweet Bakery Bread Factory - Sinta Restuasih; Ayu Nurul Haryudiniarti; Jihan Atikah Septiani (Journal of Global Engineering Research and Science, 2025)
Designing an effective factory facility layout is an important first step in establishing a manufacturing industry, including a bakery. This study aims to design the layout of PT. Golden Sweet Bakery's production facilities from scratch, starting from needs analysis, designing the production process flow, to preparing the facility layout. The design process begins with identifying space requirements based on the planned production capacity, the types of products produced, and the equipment to be used. The next stage involves analyzing the workflow to ensure efficient material flow and minimize movement. The layout is designed based on the principles of separating clean and dirty ranges, grouping similar workstations, and optimizing space use. The design results show that the designed layout can create an efficient production flow, with minimal material movement distance and optimal production cycle time. This design also considers flexibility for future expansion. With a design approach from the beginning, this design is expected to be a strong foundation for PT. Golden Sweet Bakery's operations in meeting market needs effectively. Factory layout problems are problems that cannot be avoided by companies in all their operational activities. The long distance of material movement from one department to another will affect the company's ability to increase productivity and profitability. With a high total material movement per year, material handling costs will also increase. This study aims to determine the minimum total material movement to obtain the best final layout and minimize material handling costs.